2014
DOI: 10.1682/jrrd.2013.05.0128
|View full text |Cite
|
Sign up to set email alerts
|

Sound transmission by cartilage conduction in ear with fibrotic aural atresia

Abstract: Abstract-A hearing aid using cartilage conduction (CC) has been proposed as an alternative to bone conduction (BC) hearing aids. The transducer developed for this application is lightweight, requires a much smaller fixation force than a BC hearing aid, and is more convenient to use. CC can be of great benefit to patients with fibrotic aural atresia. Fibrotic tissue connected to the ossicles provides an additional pathway (termed fibrotic tissue pathway) for sound to reach the cochlea by means of CC. To address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 24 publications
0
42
0
Order By: Relevance
“…The previous study found a great benefit of CC hearing aids, particularly to the ear with fibrotic aural atresia. Fibrotic tissue connected to the ossicles provides an additional pathway (termed fibrotic tissue pathway) for sound to reach the cochlea by means of CC [10]. Not the airborne sound but the vibration of the fibrotic tissue mediates the sound transmission in the ear with fibrotic aural atresia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous study found a great benefit of CC hearing aids, particularly to the ear with fibrotic aural atresia. Fibrotic tissue connected to the ossicles provides an additional pathway (termed fibrotic tissue pathway) for sound to reach the cochlea by means of CC [10]. Not the airborne sound but the vibration of the fibrotic tissue mediates the sound transmission in the ear with fibrotic aural atresia.…”
Section: Discussionmentioning
confidence: 99%
“…Not the airborne sound but the vibration of the fibrotic tissue mediates the sound transmission in the ear with fibrotic aural atresia. Sound in the low to middle frequency range is transmitted more efficiently by CC than BC, although the CC transducer is placed with a negligibly small fixation pressure [10]. Direct vibration of the aural cartilage is very effective form to generate not only sound but also vibration in the ear canal, which may be responsible for effective sound transmission for an acquired aural atresia with fibrotic tissue pathway [8,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1(a)]. [3][4][5][6][7][8][9][10][11][12] The transducer is composed of a piezoelectric bimorph covered in elastic material. The elastic covering broadens the spectral range of the vibration output.…”
Section: Introductionmentioning
confidence: 99%
“…For BC, although sounds are radiated into the ear canal, 12 it does not contribute to the thresholds in an open ear.involve the eardrum. Although several studies on CC have been reported, [4][5][6]14 the contribution of the pathway via the eardrum has not been revealed.…”
Section: Introductionmentioning
confidence: 99%